Life Cycle of the Dagger Nematode Xiphinema israeliae and the Host Suitability of Olive and Fig for X. israeliae and X. italiae - Emmanuel A. Tzortzakakis; Juan E. Palomares-Rius; Ana García-Velázquez; Rosana Salazar-García; Pablo Castillo; Antonio Archidona-Yuste (Agronomy)
Xiphinema israeliae has been reported in the rhizosphere of olives in Crete, Greece. Attempts were made to culture this nematode in pots planted with olive and fig seedlings, using Xiphinema index as a control. In these conditions, X. index showed a high reproduction rate on fig in a few months and none on olive. The experiments with X. israeliae indicated that olive and fig are suitable hosts for this dagger nematode, since juveniles of various life stages were found in plants inoculated exclusively with females, although the rate of nematode reproduction was low. Xiphinema israeliae was proved to have a parthenogenetic reproduction and a long life cycle, from female to female, taking more than nine months at a 24–26 °C temperature to complete. Therefore, a quite long period, even a few years, may be necessary to obtain a high number of nematodes in pots under experimental conditions. In contrast, Xiphinema italiae did not reproduce on olive and fig after a seven-month period. Accordingly, to our knowledge, this study increases the host range and knowledge about the culturing of these species, as only seven species of Xiphinema have been successfully cultured in pots till now. The potential of fig and olive for culturing X. israeliae gives an opportunity for further studies of its biology and host range.